Bridging the gap: improving CASPer test confidence and competency for underrepresented minorities in medicine through interactive peer-assisted learning - Lolade Shipeolu (Canadian Medical Education Journal, 2020)
Background: The Computer-based Assessment for Sampling Personal Characteristics (CASPer) is a situational judgement test (SJT) adopted by medical schools to assess applicants’ interpersonal skills. CASPer applicants must compose their responses to ethical dilemmas, thereby highlighting the applicant’s rationale for ethical decision-making. Minority applicants usually lack access to a network of individuals who can offer guidance and expertise on ethical decision-making. As such, this study investigated the impact of a CASPer coaching program designed for minority applicants.